2007
DOI: 10.1021/jp067156r
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Relaxation Dynamics of Acridine Orange in Nanosized Micellar Systems and DNA

Abstract: In this paper, we report a detailed study of the fluorescence relaxation dynamics of a well-known fluorescent DNA intercalator, acridine orange (AO), in reverse micelles (RM), micelles, and DNA using picosecond resolved fluorescence spectroscopy. Solvation studies of AO in AOT reverse micelles (RM) containing water indicate the locations of AO close to the interface and those in RM containing NaOH; there are two types of AO--one in the nonpolar oil phase and the other at the interface. The bound water at the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 99 publications
9
57
1
2
Order By: Relevance
“…Thus, it might be inferred that no significant change in probe location occurs upon increase in temperature, and it resides at the interface. The rotational relaxation times obtained in this study are much slower than those of rotational times reported in bulk water [155,156]. For all the studied temperatures, r(t) is characterized by a slow decay, with the presence of a considerable offset.…”
Section: Resultscontrasting
confidence: 50%
“…Thus, it might be inferred that no significant change in probe location occurs upon increase in temperature, and it resides at the interface. The rotational relaxation times obtained in this study are much slower than those of rotational times reported in bulk water [155,156]. For all the studied temperatures, r(t) is characterized by a slow decay, with the presence of a considerable offset.…”
Section: Resultscontrasting
confidence: 50%
“…One of the most extensive studies on the base content dependence of emission enhancements, quantum yields, and lifetimes for 10 monomeric and bichromophoric cyanine dyes was reported by Netzel et al 6 The differences in emission enhancement as a function of the base content for cyanine dyes complexed to dsDNA can be caused by different types of binding sites in deoxyadenosine-deoxythymidine (dAdT) and deoxyguanosine-deoxycytidine (dGdC) sequences and by different degrees of flexibility of the double helix. 17 Excited-state electron transfer (ET) quenching by nucleosides could also alter the emission enhancement. 18 ET between guanosine nucleosides is favored because this nucleoside is the easiest to oxidize.…”
Section: Introductionmentioning
confidence: 99%
“…Shaw and Pal [22] have reported the photophysics and molecular dynamics of DNA by employing Acridine Orange (AO) as a probe.…”
Section: Uv-vis Absorption Spectroscopymentioning
confidence: 99%
“…Since, it is insoluble in isooctane; it will probably be partitioned between anionic interface and water. The AO molecules in the reverse micellar media usually exhibits two peaks [22,23] (i) basic AO in the nonpolar isooctane phase ($375 nm) and (ii) protonated AO lying at the reverse micellar interface ($490 nm). The structures of AO in basic and protonated form are presented in Scheme 2.…”
Section: Uv-vis Absorption Spectroscopymentioning
confidence: 99%